Infliximab associated with faster symptom resolution compared with corticosteroids alone for the management of immune-related enterocolitis. Issue 1 (11th October 2018) - Johnson, Daniel H; Zobniw, Chrystia M; Trinh, Van A; Ma, Junsheng; Bassett, Roland L; Abdel-Wahab, Noha; Anderson, Jaime; Davis, Jennifer E; Joseph, Jocelyn; Uemura, Marc; Noman, Ali; Abu-Sbeih, Hamzah; et al.
Abstract : Background: Immune-related enterocolitis (irEC) is the most common serious complication from checkpoint inhibitors (CPIs). The current front-line treatment for irEC, high-dose corticosteroids (CS), have significant side effects and prolonged therapy may reduce CPI-anti-tumor activity. Early addition of TNF-α inhibitors such as infliximab (IFX) may expedite symptom resolution and shorten CS duration. Thus, we conducted the first retrospective study, to our knowledge, evaluating symptom resolution in patients with irEC treated with and without IFX. Methods: Data were collected from the medical records of patients diagnosed with irEC. The primary endpoint was time to symptom resolution for irEC for cases managed with IFX plus CS (IFX group) versus CS alone (CS group). Duration of CS, overall survival (OS), and time to treatment failure (TTF) were secondary endpoints. Results: Among 75 patients with irEC, 52% received CS alone, and 48% received IFX. Despite higher grade colitis in the IFX group (grade 3/4: 86% vs. 34%; p  < 0.001), median times to diarrhea resolution (3 vs. 9 days; p  < 0.001) and to steroid titration (4 vs. 13 days; p  < 0.001) were shorter in the IFX group than in the CS group without a negative impact on TTF or OS. Total steroid duration (median 35 vs. 51 days; p  = 0.150) was numerically lower in the IFX group. Conclusions: Despite higher incidence of grade 3/4 colitis, IFX added to CS for the treatment of patients with irEC was associated with a significantly shorter time to symptom resolution. The data suggest that early introduction of IFX should be considered for patients with irEC until definitive prospective clinical trials are conducted.